Electrochemical device and electronic device

By using the first polymer and carbon nanotube in the positive electrode mixture layer of the electrochemical device, the peak strength ratio of cyano and carbonyl groups to the aspect ratio of carbon nanotubes is regulated, and the conductive three-dimensional network is formed, which solves the problem of high secondary batteries. Stability and safety issues under voltage or floating charging conditions have achieved better floating charging performance, high temperature safety performance and puncture safety performance.

CN119400867AActive Publication Date: 2025-02-07NINGDE AMPEREX TECHNOLOGY LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411513824.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-02-07
Estimated Expiration
2044-10-28

AI Technical Summary

Technical Problem

Under high voltage or floating charging conditions, the complex electrochemical reactions inside the secondary battery are accelerated, limiting the working efficiency and life of the battery. Especially in the floating charging mode, the chemical imbalance of the battery intensifies, affecting stability and safety performance. .

Method used

By regulating the including the first polymer and carbon nanotube in the positive electrode mixture layer, the peak strength ratio of the cyano group and the carbon nanotube are controlled to promote electrostatic attraction between the first polymer and the carbon nanotube, and forming The conductive three-dimensional network improves the complexing effect of the positive electrode and reduces the breakage and side reaction of the positive electrode active material under floating charging, high temperature or puncture conditions.

Benefits of technology

Improves the floating charging performance, high temperature safety performance and puncture safety performance of electrochemical devices, extends the operating life of the battery and improves safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119400867A_ABST
    Figure CN119400867A_ABST
Patent Text Reader

Abstract

The invention provides an electrochemical device and an electronic device, and belongs to the technical field of electrochemistry. The electrochemical device includes a positive electrode including a positive electrode current collector and a positive electrode mixture layer disposed on at least one surface of the positive electrode current collector, the positive electrode mixture layer including a first polymer and carbon nanotubes; the first polymer comprises a nitrogen element, an oxygen element and a carbon element; the infrared spectrum of the positive electrode mixture layer comprises characteristic peaks of a cyano group and a carbonyl group, the characteristic peak of the cyano group is between 2235 cm <-1 > and 2250 cm <-1 >, and the characteristic peak of the carbonyl group is between 1675 cm <-1 > and 1700 cm <-1 >; the peak intensity ratio of the characteristic peaks of the cyano group and the carbonyl group is A, 1 < = A < = 4; and the length-diameter ratio B of the carbon nanotubes is greater than or equal to 10 and less than or equal to 500. The floating charge performance of the electrochemical device can be improved, and the high-temperature safety performance and the puncture safety performance are both improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of electrochemical technology, and specifically relates to an electrochemical device and an electronic device. Background Art

[0002] With the continuous development of portable electronic devices and electric vehicle markets, higher requirements are placed on the energy density and charging efficiency of secondary batteries. This trend has promoted a significant increase in battery voltage and charging rate to meet the urgent demand for longer battery life and shorter charging time for electronic devices.

[0003] However, under high voltage or floating charge conditions, complex electrochemical reactions will accelerate inside the secondary battery, limiting the battery's operating efficiency and life. Especially in floating charge mode, when the battery is kept close to full charge for a long time without being fully discharged, the chemical imbalance inside the battery is aggravated, which will affect the stability and safety performance of the secondary battery. Therefore, how to improve the stability and safety performance of secondary batteries has become a key technical issue that needs to be solved in the current secondary battery field. Summary of the invention

[0004] In view of this, the present application provides an electrochemical device and an electronic device, which can improve the floating charge performance of the electrochemical device by regulating the positive electrode mixture layer to include a first polymer and carbon nanotubes, while also improving high temperature safety performance and puncture safety performance.

[0005] In a first aspect, the present application provides an electrochemical device, including a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode includes a positive electrode current collector and a positive electrode mixture layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode mixture layer includes a first polymer and carbon nanotubes; the first polymer includes nitrogen, oxygen and carbon; the infrared spectrum of the positive electrode mixture layer includes characteristic peaks of cyano and carbonyl, wherein the characteristic peak of cyano is located at 2235 cm -1 Up to 2250cm -1 The characteristic peak of carbonyl is located at 1675 cm -1 Up to 1700cm -1 ; The peak intensity ratio of the characteristic peaks of cyano and carbonyl is A, 1≤A≤4; the aspect ratio of carbon nanotubes is B, 10≤B≤500. The present application controls the positive electrode mixture layer to include a first polymer and carbon nanotubes, wherein the first polymer has cyano and carbonyl groups, and by controlling the peak intensity ratio of cyano and carbonyl groups and coordinating with the aspect ratio of carbon nanotubes, the electrostatic attraction between the first polymer and the carbon nanotubes can be promoted, thereby forming a conductive three-dimensional network of the first polymer-positive electrode active material-carbon nanotubes on the surface of the positive electrode active material, improving the complexing effect of the positive electrode, and thereby reducing the breakage of the positive electrode active material under floating charge, high temperature or puncture conditions and the side reaction with the electrolyte, thereby improving the floating charge performance, high temperature safety performance and puncture safety performance of the electrochemical device.

[0006] In some embodiments, the electrochemical device satisfies at least one of the following conditions: (1) 150≤A×B≤400; (2) 1≤A≤2; (3) 100≤B≤300. Regulating the peak intensity ratio of the cyano group and the carbonyl group and the aspect ratio of the carbon nanotube to meet the above conditions can promote better coordination between the first polymer and the carbon nanotube, and further improve the floating charge performance, high temperature safety performance and puncture safety performance of the electrochemical device.

[0007] In some embodiments, the positive electrode mixture layer also includes lithium cobalt oxide. Based on the total number of particles in the positive electrode mixture layer, the number of particles of the first polymer accounts for K1%, and the number of particles of the lithium cobalt oxide accounts for K2%, and 33≤K2 / K1≤10000. The inventors have found that under floating charge, high temperature or puncture conditions, the lithium cobalt oxide of the positive electrode is prone to rapid heat and gas generation reactions with the electrolyte, affecting the floating charge performance and safety performance of the electrochemical device. The present application controls the number of particles of lithium cobalt oxide and the first polymer to satisfy the above relationship, thereby improving the complexation effect of the conductive three-dimensional network of the first polymer-lithium cobalt oxide-carbon nanotubes, reducing the fragmentation of lithium cobalt oxide under the above conditions and the side reactions with the electrolyte, and further improving the floating charge performance, high temperature safety performance and puncture safety performance of the electrochemical device.

[0008] In some embodiments, 0.01≤K1≤1; and / or, 98≤K2≤99. When the ratio of the number of particles of the first polymer and the lithium cobalt oxide is adjusted to meet the above range, the coordination effect of the first polymer and the lithium cobalt oxide can be improved, and the floating charge performance, high temperature safety performance and puncture safety performance of the electrochemical device can be better improved.

[0009] In some embodiments, from the perspective of improving the floating charge performance, high temperature safety performance and puncture safety performance of the electrochemical device, based on the total mass of carbon, nitrogen and oxygen elements, the first polymer satisfies at least one of the following conditions: (1) the mass proportion of the nitrogen element is H1%, 5≤H1≤20; (2) the mass proportion of the oxygen element is H2%, 5≤H2≤20; (3) the mass proportion of the carbon element is H3%, 60≤H3≤90.

[0010] In some embodiments, the first polymer includes a first monomer, a second monomer and a third monomer; the first monomer is selected from at least one of acrylonitrile or methacrylonitrile; the second monomer is selected from at least one of methyl acrylate, ethyl acrylate, propyl acrylate, isopropyl acrylate, isobutyl acrylate, tert-butyl acrylate, isopentyl acrylate, n-hexyl acrylate, 2-ethylhexyl acrylate, methyl methacrylate, ethyl methacrylate, propyl methacrylate, isopropyl methacrylate, isobutyl methacrylate, tert-butyl methacrylate, isopentyl methacrylate, n-hexyl methacrylate or 2-ethylhexyl methacrylate; the third monomer is selected from at least one of acrylic acid, methacrylic acid, lithium acrylate, sodium acrylate, lithium methacrylate or sodium methacrylate.

[0011] In the present application, the first polymer includes the first monomer, the second monomer and the third monomer, which means that the first polymer is obtained by copolymerizing the first monomer, the second monomer and the third monomer. Taking the first monomer as an example, based on the mass of the first polymer, the mass proportion of the first monomer refers to the mass proportion of the unit formed after the polymerization of the first monomer in the first polymer.

[0012] In some embodiments, based on the mass of the first polymer, the first polymer satisfies at least one of the following conditions: (1) the mass proportion of the first monomer is M1%, 50≤M1≤90; (2) the mass proportion of the second monomer is M2%, 1≤M2≤30; (3) the mass proportion of the third monomer is M3%, 5≤M3≤30; the present application regulates the mass proportions of each monomer in the first polymer to meet the above ranges, wherein the first monomer can dominate the complexation with the transition metal of the positive electrode active material, thereby reducing the impact and damage of high voltage on the positive electrode particles; the second monomer can provide adhesion, so that the polymer can interact with the positive electrode particles with a relatively strong physical adhesion; the third monomer can enhance the flexibility of the molecule, so that when the cold pressing causes the electrode to be exposed to a large pressure, the positive electrode particles will not be crushed to the point of being crushed, but will have a certain buffer, and through the mutual cooperation between the monomers, the floating charge performance, high temperature safety performance and puncture safety performance of the electrochemical device are further improved.

[0013] In some embodiments, the first polymer also includes a fourth monomer, and the fourth monomer is selected from at least one of acrylamide, N-methylacrylamide, N-ethylacrylamide or 2-methylacrylamide. Based on the mass of the first polymer, the mass proportion of the fourth monomer is M4%, 0.01≤M4≤15, preferably 1≤M4≤15. The present application regulates the further addition of a fourth monomer to the first polymer, and controls the mass proportion of the fourth monomer to meet the above range. The amide can have a certain π-π attraction with the nitrile in the first monomer, and after combining with the carbon nanotubes, it can be expanded to form a larger positive electrode attraction conductive network, so that the positive electrode material has better high voltage and high temperature resistance, and further improves the floating charge performance, high temperature safety performance and puncture safety performance of the electrochemical device.

[0014] In some embodiments, the maximum particle size of the first polymer is Dμm, 15≤D≤100; preferably 15≤D≤50. When the maximum particle size of the first polymer is within the above range, it can be close to the positive electrode material particles, and the elements of the polymer can interact with the positive electrode elements at the same scale. And under the above size, it can match the size of the pole piece, reduce the particle breakage caused by the cold pressing process of the pole piece, which is beneficial to improve the stability of the first polymer particles, and can also optimize the coating effect on the positive electrode active material particles, reduce the occurrence of side reactions, thereby further improving the floating charge performance, high temperature safety performance and puncture safety performance of the electrochemical device.

[0015] In some embodiments, the electrolyte includes linear carbonates, and the linear carbonates include ethylene carbonate, propylene carbonate, and fluoroethylene carbonate. The present application further controls the electrolyte to include ethylene carbonate, propylene carbonate, and fluoroethylene carbonate, which can promote the electrostatic coupling between polar groups of the electrolyte and the oxygen-containing and nitrogen-containing functional groups of the polymer, so that the solid polymer is softened to a certain extent under the action of the electrolyte, and the contact area between the softened polymer and the positive electrode particles will increase, and the contact effect will also be improved to a certain extent, further improving the floating charge performance, high temperature safety performance, and puncture safety performance of the electrochemical device.

[0016] In a second aspect, the present application provides an electronic device comprising any one of the above-mentioned electrochemical devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is an infrared spectrum of the positive electrode mixture layer in the electrochemical device of Example 1-1 of the present application;

[0018] Figure 2 This is a scanning electron microscope image of the first polymer of the present application. DETAILED DESCRIPTION

[0019] In order to make the purpose, technical solution and advantages of the present application more clear, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described here are only used to explain the present application and are not used to limit the present application.

[0020] In a first aspect, the present application provides an electrochemical device, including a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode includes a positive electrode current collector and a positive electrode mixture layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode mixture layer includes a first polymer and carbon nanotubes; the first polymer includes nitrogen, oxygen and carbon; the infrared spectrum of the positive electrode mixture layer includes characteristic peaks of cyano and carbonyl, wherein the characteristic peak of cyano is located at 2235 cm -1 Up to 2250cm -1 The characteristic peak of carbonyl is located at 1675 cm -1 Up to 1700cm -1 ; The peak intensity ratio of the characteristic peaks of cyano and carbonyl is A, 1≤A≤4; the aspect ratio of carbon nanotubes is B, 10≤B≤500. The present application controls the positive electrode mixture layer to include a first polymer and carbon nanotubes, wherein the first polymer has cyano and carbonyl groups, and by controlling the peak intensity ratio of cyano and carbonyl groups and coordinating with the aspect ratio of carbon nanotubes, the electrostatic attraction between the first polymer and the carbon nanotubes can be promoted, thereby forming a conductive three-dimensional network of the first polymer-positive electrode active material-carbon nanotubes on the surface of the positive electrode active material, improving the complexing effect of the positive electrode, and thereby reducing the breakage of the positive electrode active material under floating charge, high temperature or puncture conditions and the side reaction with the electrolyte, thereby improving the floating charge performance, high temperature safety performance and puncture safety performance of the electrochemical device.

[0021] In some embodiments, 150≤A×B≤400; for example, the value of A×B is 150, 160, 170, 200, 230, 240, 250, 270, 300, 320, 330, 360, 370, 400 or a value in the range formed by any two of these values. Regulating the peak intensity ratio of cyano and carbonyl groups and the aspect ratio of carbon nanotubes to satisfy the above relationship can further improve the floating charge performance, high temperature safety performance and puncture safety performance of the electrochemical device.

[0022] In some embodiments, 1≤A≤4, preferably 1≤A≤2. For example, A is 1, 1.2, 1.3, 1.5, 1.8, 2.1, 2.3, 2.6, 2.8, 3.0, 3.1, 3.4, 3.7, 4, or a value in the range of any two of these values. By regulating the peak intensity ratio of cyano and carbonyl to meet the above conditions, the floating charge performance, high temperature safety performance, and puncture safety performance of the electrochemical device can be further improved.

[0023] In some embodiments, 10≤B≤500, preferably 100≤B≤300. For example, B is 10, 70, 110, 150, 160, 200, 250, 280, 330, 360, 400, 450, 490, 500, or a value in the range formed by any two of these values. Regulating the aspect ratio of the carbon nanotubes to meet the above conditions can further improve the floating charge performance, high temperature safety performance, and puncture safety performance of the electrochemical device.

[0024] In some embodiments, the positive electrode mixture layer also includes lithium cobalt oxide, and based on the total number of particles in the positive electrode mixture layer, the number of particles of the first polymer accounts for K1%, and the number of particles of the lithium cobalt oxide accounts for K2%, and 33≤K2 / K1≤10000. For example, the value of K2 / K1 is 33, 462, 1029, 2242, 2353, 3291, 4016, 5090, 5897, 6820, 7469, 7776, 8695, 9407, 10000 or a value in the range composed of any two of these values. The present application controls the number of particles of lithium cobalt oxide and the first polymer to meet the above relationship, thereby improving the complexing effect of the conductive three-dimensional network of the first polymer-lithium cobalt oxide-carbon nanotubes, reducing the fragmentation of lithium cobalt oxide under the above conditions and the side reaction with the electrolyte, and further improving the floating charge performance, high temperature safety performance and puncture safety performance of the electrochemical device.

[0025] In some embodiments, 0.01≤K1≤1, for example, the value of K1 is 0.01, 0.09, 0.16, 0.22, 0.25, 0.35, 0.43, 0.49, 0.62, 0.64, 0.74, 0.82, 0.86, 0.99, 1, or a value in the range of any two of these values. When the proportion of the number of particles of the first polymer is adjusted to meet the above range, the floating charge performance, high temperature safety performance and puncture safety performance of the electrochemical device can be better improved.

[0026] In some embodiments, 98≤K2≤99, for example, the value of K2 is 98, 98.04, 98.10, 98.22, 98.26, 98.34, 98.43, 98.48, 98.57, 98.62, 98.71, 98.80, 98.89, 98.93, 99 or a value in the range formed by any two of these values. When the particle number ratio of lithium cobalt oxide is adjusted to meet the above range, the floating charge performance, high temperature safety performance and puncture safety performance of the electrochemical device can be better improved.

[0027] In some embodiments, the first polymer includes a first monomer, a second monomer and a third monomer; the first monomer is selected from at least one of acrylonitrile or methacrylonitrile; the second monomer is selected from at least one of methyl acrylate, ethyl acrylate, propyl acrylate, isopropyl acrylate, isobutyl acrylate, tert-butyl acrylate, isopentyl acrylate, n-hexyl acrylate, 2-ethylhexyl acrylate, methyl methacrylate, ethyl methacrylate, propyl methacrylate, isopropyl methacrylate, isobutyl methacrylate, tert-butyl methacrylate, isopentyl methacrylate, n-hexyl methacrylate or 2-ethylhexyl methacrylate; the third monomer is selected from at least one of acrylic acid, methacrylic acid, lithium acrylate, sodium acrylate, lithium methacrylate or sodium methacrylate.

[0028] In some embodiments, based on the mass of the first polymer, the first polymer satisfies at least one of the following conditions: (1) the mass proportion of the first monomer is M1%, 50≤M1≤90, for example, the value of M1 is 50, 52, 55, 57, 61, 63, 68, 71, 73, 77, 78, 84, 86, 87, 90 or a value within the range of any two of these values; (2) the mass proportion of the second monomer is M2%, 1≤M2≤30, for example, the value of M2 is 1, 2, 4, 6, 9, 11, 12, 15, 17, 19, 22, 24, 26, 29, 30 or a value within the range formed by any two of these values; (3) the mass proportion of the third monomer is M3%, 5≤M3≤30, for example, the value of M3 is 5, 8, 9, 12, 15, 15, 17, 19, 21, 24, 26, 28, 29, 30 or a value within the range formed by any two of these values; the present application regulates the mass proportion of each monomer in the first polymer to meet the above-mentioned ranges, respectively, which can further improve the floating charge performance, high temperature safety performance and puncture safety performance of the electrochemical device.

[0029] In some embodiments, the first polymer also includes a fourth monomer, and the fourth monomer is selected from at least one of acrylamide, N-methylacrylamide, N-ethylacrylamide or 2-methylacrylamide. Based on the mass of the first polymer, the mass proportion of the fourth monomer is M4%, 1≤M4≤15, for example, the value of M4 is 1, 2, 3, 4, 5, 6, 8, 9, 10, 11, 12, 14, 15 or a value within the range composed of any two of these values. The present application regulates the first polymer to further include a fourth monomer, and regulates the mass proportion to meet the above range, which can further improve the floating charge performance, high temperature safety performance and puncture safety performance of the electrochemical device.

[0030] In the present application, the first polymer is prepared by a method comprising the following steps: under an inert gas atmosphere, the first monomer, the second monomer and the third monomer are added to a dispersion medium (if there is a fourth monomer, it can also be added in this step), the temperature is raised to 55-80°C, and then an initiator is added to carry out a copolymerization reaction, and the copolymerization reaction time is 3-10 hours to obtain the first polymer. In order to better exert the effect of the first polymer, the first polymer can be neutralized to a pH of 7-7.8, and then dried and crushed.

[0031] The present application has no special requirements for the dispersion medium, as long as it can dissolve or disperse the monomers in the present application, for example, it can be water or an organic solvent.

[0032] In some specific embodiments, the first polymer can be prepared by a method comprising the following steps: placing the solvent in a 2000L reactor at room temperature, introducing nitrogen with a purity of ≥99.9% under stirring at a speed of 100-300rpm, and controlling the flow rate at 2000-4000L / H. After displacement for 1h, remove the water-soluble oxygen, and add 60% acrylic acid, 20% methyl acrylate, and 20% methacrylic acid by mass percentage; maintaining the nitrogen atmosphere, heating the solution to 65°C at a heating rate of 1-2°C / min, adding 0.1wt% ammonium persulfate, keeping the temperature stable, reacting for 5h, copolymerizing, and obtaining the first polymer. Then, at 60°C, neutralize with an alkaline aqueous solution to a pH of 7.5 to obtain a film. Then, dry the film in an oven at 120°C for 24h. Transfer the dried film to a FRITSCH grinder, and grind the film into powder at a speed of 400rpm.

[0033] In some embodiments, the maximum particle size of the first polymer is D μm, 15≤D≤100; preferably 15≤D≤50, for example, D is 15, 17, 25, 33, 38, 45, 50, 55, 66, 68, 76, 81, 88, 99, 100 or a value in the range formed by any two of these values. When the maximum particle size of the first polymer is within the above range, the floating charge performance, high temperature safety performance and puncture safety performance of the electrochemical device can be further improved.

[0034] In the present application, the positive electrode includes a positive electrode current collector and a positive electrode mixture layer arranged on at least one surface of the positive electrode current collector. The above-mentioned "positive electrode mixture layer arranged on at least one surface of the positive electrode current collector" means that the positive electrode mixture layer can be located on one surface of the positive electrode current collector along its own thickness direction, or on two surfaces of the positive electrode current collector along its own thickness direction. It should be noted that the "surface" here can be the entire area of ​​the surface of the positive electrode current collector, or it can be a partial area of ​​the surface of the positive electrode current collector. This application has no special restrictions, as long as the purpose of this application can be achieved. This application has no special restrictions on the positive electrode current collector, as long as the purpose of this application can be achieved. For example, the positive electrode current collector may include aluminum foil, aluminum alloy foil or a composite current collector (such as an aluminum-carbon composite current collector). In the present application, the positive active material may also include non-metallic elements, for example, non-metallic elements include at least one of fluorine, phosphorus, boron, chlorine, silicon, and sulfur.

[0035] In the present application, the positive electrode mixture layer may also include a positive electrode binder. The present application does not particularly limit the type of positive electrode binder in the positive electrode mixture layer, as long as the purpose of the present application can be achieved. For example, the positive electrode binder may include but is not limited to polyvinylidene fluoride, polytetrafluoroethylene, polyolefins, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, modified polyvinylidene fluoride, modified styrene-butadiene rubber (SBR) or at least one of polyurethane. In some embodiments, the polyolefin binder includes at least one of polyethylene, polypropylene, polyolefin ester, polyolefin alcohol or polyacrylic acid. The present application does not particularly limit the thickness of the positive electrode mixture layer, as long as the purpose of the present application can be achieved. For example, the thickness of the positive electrode mixture layer may be 3μm to 15μm.

[0036] In some embodiments, the electrolyte includes ethylene carbonate, propylene carbonate and fluoroethylene carbonate. The present application further controls the electrolyte to include ethylene carbonate, propylene carbonate and fluoroethylene carbonate, which can further improve the floating charge performance, high temperature safety performance and puncture safety performance of the electrochemical device.

[0037] According to some embodiments of the present application, the electrolyte further includes a lithium salt and a non-aqueous solvent. The lithium salt may include, but is not limited to, at least one of lithium hexafluorophosphate (LiPF6), lithium bis(trifluoromethanesulfonyl)imide LiN(CF3SO2)2(LiTFSI), lithium bis(fluorosulfonyl)imide Li(N(SO2F)2)(LiFSI), lithium bis(oxalate borate) LiB(C2O4)2(LiBOB), lithium difluorooxalate borate LiBF2(C2O4)(LiDFOB), LiNO3, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3, LiC(SO2CF3)3, and Li2SiF6. The present application does not limit the content of the lithium salt in the electrolyte, as long as the purpose of the present application can be achieved. The present application has no special restrictions on the non-aqueous solvent, as long as the purpose of the present application can be achieved. For example, the non-aqueous solvent may include, but is not limited to, at least one of a cyclic carbonate compound, a carboxylate compound, an ether compound, or other organic solvents. The above-mentioned cyclic carbonate compound and the above-mentioned carboxylate compound include at least one of methyl formate, methyl acetate, methyl propionate, methyl butyrate, ethyl formate, ethyl acetate, ethyl propionate, ethyl butyrate, propyl formate, propyl acetate, propyl propionate, propyl butyrate, butyl butyrate, butyl propionate, and pentyl propionate. The above-mentioned ether compound may include but is not limited to at least one of 1,3-dioxolane (DOL), ethylene glycol dimethyl ether (1,2-dimethoxyethane, DME), dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-diethoxyethane, 1-ethoxy-1-methoxyethane, 2-methyltetrahydrofuran or tetrahydrofuran. The above-mentioned other organic solvents may include but are not limited to at least one of dimethyl sulfoxide, 1,2-dioxolane, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate or trioctyl phosphate.

[0038] The present application has no special restrictions on the negative electrode sheet, as long as the purpose of the present application can be achieved. For example, the negative electrode sheet includes a negative electrode current collector and a negative electrode mixture layer arranged on at least one surface of the negative electrode current collector. In the present application, the negative electrode mixture layer can be arranged on one surface in the thickness direction of the negative electrode current collector, or on two surfaces in the thickness direction of the negative electrode current collector. It should be noted that the "surface" here can be the entire area of ​​the negative electrode current collector or a partial area of ​​the negative electrode current collector. The present application has no special restrictions, as long as the purpose of the present application can be achieved. The present application has no special restrictions on the negative electrode current collector, as long as the purpose of the present application can be achieved. For example, it may include but is not limited to copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, foamed nickel, foamed copper or composite current collector (such as carbon copper composite current collector, nickel copper composite current collector, titanium copper composite current collector, etc.). In the present application, there are no special restrictions on the thickness of the negative electrode current collector, the negative electrode mixture layer and the negative electrode sheet, as long as the purpose of the present application can be achieved.

[0039] The negative electrode mixture layer of the present application includes a negative electrode active material, and the negative electrode active material may include but is not limited to graphite, mesophase microcarbon beads (MCMB), hard carbon, soft carbon, silicon, silicon-carbon composites, SiO x (0.5<x<1.6), Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, spinel structure lithium titanate TiO2-Li4Ti5O 12 , at least one of Li-Al alloy and metallic lithium.

[0040] The negative electrode mixture layer in the present application may also include a negative electrode binder and a negative electrode conductor, or the negative electrode mixture layer may also include a negative electrode binder, a negative electrode conductor and a thickener. The present application has no particular restrictions on the types of negative electrode binders and negative electrode conductors, as long as the purpose of the present application can be achieved. For example, the negative electrode binder may include but is not limited to at least one of the above-mentioned positive electrode binders, and the negative electrode conductor may include but is not limited to at least one of the above-mentioned positive electrode conductors. The present application has no particular restrictions on the types of thickeners, as long as the purpose of the present application can be achieved. For example, the thickener may include but is not limited to at least one of sodium carboxymethyl cellulose or carboxymethyl cellulose. The present application has no particular restrictions on the mass ratio of the negative electrode active material, the negative electrode conductor, the negative electrode binder, and the thickener in the negative electrode mixture layer. Those skilled in the art can choose according to actual needs, as long as the purpose of the present application can be achieved.

[0041] The electrochemical device of the present application may also include an isolating membrane, and the present application has no particular restrictions on the isolating membrane, as long as the purpose of the present application can be achieved. For example, the material of the isolating membrane may include, but is not limited to, polyethylene (PE), polypropylene (PP)-based polyolefins (PO), polyesters (such as polyethylene terephthalate (PET) films), cellulose, polyimide (PI), polyamide (PA), spandex, and at least one of aramid; the type of isolating membrane may include at least one of woven membranes, non-woven membranes, microporous membranes, composite membranes, rolled membranes, and spinning membranes. For example, the isolating membrane may include a substrate layer and a surface treatment layer. The substrate layer may be a non-woven fabric, a membrane, or a composite membrane having a porous structure, and the material of the substrate layer may include at least one of polyethylene, polypropylene, polyethylene terephthalate, and polyimide. Optionally, a polypropylene porous membrane, a polyethylene porous membrane, a polypropylene non-woven fabric, a polyethylene non-woven fabric, or a polypropylene-polyethylene-polypropylene porous composite membrane may be used. Optionally, a surface treatment layer is provided on at least one surface of the substrate layer, and the surface treatment layer may be a polymer layer or an inorganic layer, or a layer formed by a mixed polymer and an inorganic material. For example, the inorganic layer includes inorganic particles and a binder, and the present application has no particular restrictions on the inorganic particles, for example, it may include at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide, and barium sulfate. The present application has no particular restrictions on the binder, for example, it may be at least one of the above-mentioned positive electrode binders. The polymer layer contains a polymer, and the present application has no particular restrictions on the polymer, for example, the polymer includes at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylate, polyvinyl pyrrolidone, polyvinyl ether or polyvinylidene fluoride and poly (vinylidene fluoride-hexafluoropropylene). In the present application, the thickness of the separator is not particularly limited, as long as the purpose of the present application can be achieved, for example, the thickness of the separator may be 5 μm to 500 μm.

[0042] The electrochemical device of the present application also includes a packaging bag for containing a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, as well as other components known in the art in the electrochemical device, and the present application does not limit the above other components. The present application does not specifically limit the packaging bag, and it can be a packaging bag known in the art, as long as it can achieve the purpose of the present application.

[0043] The electrochemical device of the present application is not particularly limited, and may include any device that undergoes an electrochemical reaction. In one embodiment of the present application, the electrochemical device may include, but is not limited to, a lithium ion battery, a sodium ion battery, and the like.

[0044] The present application does not particularly limit the preparation method of the electrochemical device, for example, it may include the following steps: stacking the positive electrode sheets, the separator and the negative electrode sheets in order, and winding, folding and other operations as needed to obtain an electrode assembly with a wound structure, placing the electrode assembly in a packaging bag, injecting an electrolyte into the packaging bag and sealing it to obtain an electrochemical device; or, stacking the positive electrode sheets, the separator and the negative electrode sheets in order, and then fixing the four corners of the entire stacked structure to obtain an electrode assembly with a stacked structure, placing the electrode assembly in a packaging bag, injecting an electrolyte into the packaging bag and sealing it to obtain an electrochemical device.

[0045] In a second aspect, the present application provides an electronic device comprising any one of the above-mentioned electrochemical devices.

[0046] The electronic device of the present application is not particularly limited, and it can be used for any electronic device known in the prior art. For example, the electronic device can include but is not limited to a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, a liquid crystal television, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery, and a lithium-ion capacitor.

[0047] The scheme of the present application is described below by taking lithium-ion batteries as an example and combining the following specific embodiments. Unless otherwise specified, the raw materials used in the following embodiments are all from common commercial products, and the devices or equipment used are all purchased from conventional market sales channels.

[0048] Test Method

[0049] Carbon nanotube aspect ratio test

[0050] The positive electrode sheet is observed using SEM, and the lengths and diameters of at least 20 carbon nanotubes are counted to calculate the average length and diameter. Then, the aspect ratio of the carbon nanotubes is calculated based on the average length and diameter.

[0051] Particle count test

[0052] The positive electrode sheet was observed using a scanning electron microscope (SEM) in backscatter mode with a total area of ​​2000 μm 2 The area is the test area, and the arithmetic mean is calculated according to the ratio of the number of lithium cobalt oxide particles and the number of first polymer particles in the test area to obtain the final particle number ratio.

[0053] Maximum particle size test

[0054] Observe the first polymer particles separated from the positive electrode sheet or the first polymer in the positive electrode sheet in the SEM backscattering mode, and select the first polymer material with the largest longest diameter in the field of view. The longest diameter of the first polymer material is the maximum particle size of the first polymer. Figure 2 The scanning electron microscope image (SEM image) of the first polymer of the present application is shown. As shown in the figure, the maximum particle size of the first polymer particles in this batch is 32.0 μm. When observing the positive electrode sheet, the actual area corresponding to the total observation field of view should be greater than 2000 μm. 2 .

[0055] Float charge test

[0056] (1) Place the lithium-ion battery in an environment at 45°C for 5 minutes;

[0057] (2) The battery is charged at a constant current of 0.7C to a full charge voltage of 4.53V, and at a constant voltage of 60mA at the maximum voltage; the initial thickness d0 of the lithium-ion battery is tested;

[0058] (3) Charge the battery at a constant voltage of 4.53V for 70 days and charge to 100mA; (4) Every 4 days, use the test probe of the voltage internal resistance meter to directly connect the positive and negative electrodes of the lithium-ion battery to measure the voltage internal resistance of the lithium-ion battery (1KHz frequency), and use a flat thickness gauge (with 500g pressure) to measure the battery thickness d1. The thickness growth rate = battery thickness d1 / initial thickness d0×100%. When the battery thickness growth rate exceeds 40% compared to the initial growth rate, stop the test.

[0059] (5) The thickness growth rate on the 32nd day is defined as the floating charge performance characterization point, that is, the floating charge thickness growth rate = battery thickness d1 on the 32nd day / initial thickness d0×100%.

[0060] Puncture safety test

[0061] (1) Place the lithium-ion battery in an environment at 25°C for 5 minutes.

[0062] (2) The battery was discharged at a constant current of 0.2C to a voltage of 3.0V and then left to stand for 10 minutes.

[0063] (3) The battery was charged at a constant current of 0.7C to a full charge voltage of 4.53V, and then charged at a constant voltage at the maximum voltage until the current reached 0.025C, and then left to stand for 10 minutes.

[0064] (4) Take a photo of the lithium-ion battery, use the test probe of the voltage internal resistance meter to directly connect the positive and negative electrodes of the lithium-ion battery, and measure the voltage internal resistance of the lithium-ion battery (1kHz frequency).

[0065] (5) Stick the temperature-sensing wire on the surface of the lithium-ion battery, place the lithium-ion battery on the test table in a test environment of 20±5℃, and use a 3mm diameter straight nail to test from the center of the lithium-ion battery at a speed of 150mm / s. The lithium-ion battery is completely pierced by the straight nail and photographed after being kept for 30 minutes. The voltage internal resistance of the lithium-ion battery is measured again using a voltage internal resistance meter. If the battery does not catch fire or explode before the nail is pulled out, it indicates that the lithium-ion battery has passed the puncture performance test, which is recorded as P (Pass). In the test results, 3 / 10P means that 3 out of 10 products passed the test, and 0 / 10P means that 0 out of 10 products passed the test.

[0066] The high temperature safety test (i.e. hot box test) process is as follows:

[0067] (I) Adjust the furnace temperature to 25°C and place the lithium-ion battery to be tested in the heating furnace box for 5 minutes;

[0068] (II) 0.2C constant current discharge (DC) to 3.0V;

[0069] (III) Leave to stand for 10 min;

[0070] (IV) 0.7C constant current charge (CC) to 4.53V, then constant voltage charge (CV) to 0.025C;

[0071] (V) Let stand for 10 minutes.

[0072] Take photos before the test, measure the voltage and internal resistance, and attach the temperature-sensing wire to the surface of the battery. Put the sample into the heating furnace, heat it to 130℃ (or 132℃) at a heating rate of 5±2℃ / min and keep it for 60 minutes. Take photos after the test and measure the voltage and internal resistance. If the battery does not catch fire or explode, it means that it has passed the hot box test, which is recorded as P (Pass). In the test results, 3 / 5P means that 3 out of 5 products passed the test, and 0 / 5P means that 0 out of 5 products passed the test.

[0073] Example 1-1

[0074] The lithium-ion battery of this embodiment includes a positive electrode, a negative electrode and an electrolyte, the positive electrode includes a positive electrode current collector and a positive electrode mixture layer disposed on at least one surface of the positive electrode current collector, and the positive electrode mixture layer includes a first polymer and carbon nanotubes; Figure 1 The infrared spectrum of the positive electrode mixture layer is shown, and the characteristic peaks of cyano and carbonyl can be seen. The characteristic peak of cyano is located at 2235cm -1 Up to 2250cm -1 The characteristic peak of carbonyl is located at 1675 cm -1 Up to 1700cm -1; The peak intensity ratio of the characteristic peaks of cyano and carbonyl is A, A=1.6; the aspect ratio of carbon nanotubes is B, B=150, A×B=240.

[0075] The positive electrode mixture layer also includes lithium cobalt oxide. Based on the total number of particles in the positive electrode mixture layer, the number of particles of the first polymer accounts for K1% of 2.88%, the number of particles of lithium cobalt oxide accounts for K2% of 95%, and K2 / K1=33. The first polymer includes a first monomer, a second monomer and a third monomer. The first monomer is acrylonitrile, accounting for M1% of 60% by mass, the second monomer is methyl acrylate, accounting for M2% of 10% by mass, and the third monomer is acrylic acid, accounting for M3% of 30% by mass. The maximum particle size Dμm of the first polymer is 110μm.

[0076] Preparation of negative electrode

[0077] The negative electrode active material graphite particles, binder styrene butadiene rubber (SBR), and thickener sodium carboxymethyl cellulose (CMC) were fully stirred and mixed in a solvent deionized water according to a weight ratio of 97.4:1.4:1.2 to form a uniform negative electrode slurry (solid content 42%). The negative electrode slurry was evenly coated on a 5um thick negative electrode current collector copper foil, dried, and cold pressed to form a 110μm negative electrode active material layer, and then cut and welded to the tabs to obtain the negative electrode sheet.

[0078] Preparation of positive electrode

[0079] The positive electrode active material lithium cobalt oxide, the conductive agent acetylene black, the binder polyvinylidene fluoride (PVDF) and the first polymer are mixed in a solvent N-methylpyrrolidone (NMP) at a mass ratio of 97.2:1.3:1.3:0.2, and fully stirred in a vacuum mixer to obtain a positive electrode slurry (solid content 69%). The positive electrode material is coated on a 10um thick positive electrode current collector aluminum foil, dried, and cold pressed to form a positive electrode active material layer of about 80um thick, and then cut into pieces and welded to the pole ears to obtain a positive electrode sheet.

[0080] Preparation of electrolyte

[0081] In a dry argon atmosphere glove box, ethylene carbonate (EC) and propylene carbonate (PC) were mixed evenly at a mass ratio of EC:PC=55:45, and then fluoroethylene carbonate was added, dissolved and fully stirred, and then lithium salt LiPF6 was added and mixed evenly to obtain an electrolyte. Among them, based on the mass of the electrolyte, the mass percentage of LiPF6 is 12.5%, and the mass percentage of fluoroethylene carbonate is 5%.

[0082] Preparation of isolation membrane

[0083] A polyethylene (PE) porous polymer film is used as the isolation membrane.

[0084] Preparation of lithium-ion batteries

[0085] The obtained positive electrode, isolation film, and negative electrode are stacked in order, so that the isolation film is placed between the positive electrode and the negative electrode to play an isolating role, and then wound to obtain a bare cell; the bare cell is placed in an outer packaging foil aluminum-plastic film, and the electrolyte is injected. After vacuum packaging, standing, formation and other process flows, a lithium-ion battery is obtained.

[0086] The lithium-ion batteries of the embodiments and comparative examples in Table 1 differ from those of Embodiment 1-1 mainly in that the peak intensity ratio A of the characteristic peaks of the cyano group and the carbonyl group, the aspect ratio B of the carbon nanotubes, and the types and mass proportions of the monomers of the first polymer are adjusted according to Table 1. The specific adjustment parameters and performance test results are shown in Table 1.

[0087] Table 1

[0088]

[0089]

[0090] Note: () indicates the mass proportion of each monomer in the first polymer.

[0091] As can be seen from Table 1, the present application can improve the floating charge performance, high temperature safety performance and puncture safety performance of the electrochemical device by regulating the peak intensity ratio of the amino group and the carbonyl group in the first polymer in the positive electrode mixture layer and coordinating with the aspect ratio of the carbon nanotubes. In particular, when the peak intensity ratio of the cyano group and the carbonyl group and the aspect ratio of the carbon nanotubes are regulated to meet the above ranges, the floating charge performance, high temperature safety performance and puncture safety performance of the electrochemical device can be further improved.

[0092] In particular, when the types and mass proportions of the first monomer, the second monomer and the third monomer in the first polymer are regulated to meet the above ranges, the floating charge performance, high temperature safety performance and puncture safety performance of the electrochemical device can be further improved through the mutual cooperation between the monomers. In particular, when the first polymer also includes the fourth monomer, the mass proportion of the fourth monomer is regulated to meet the above ranges, and it can be combined with the carbon nanotubes, thereby making the electrochemical device exhibit more excellent floating charge performance, high temperature safety performance and puncture safety performance.

[0093] The lithium-ion batteries of the embodiments and comparative examples in Table 2 differ from those of Embodiments 1-5 mainly in that the particle number proportion K1% of the first polymer, the particle number proportion K2% of the lithium cobalt oxide, and the maximum particle size Dμm of the first polymer are adjusted according to Table 2. The specific adjustment parameters and performance test results are shown in Table 2.

[0094] Table 2

[0095]

[0096]

[0097] As can be seen from Table 2, the present application regulates the number of particles of the first polymer and lithium cobalt oxide in the positive electrode mixture layer and their relationship to meet the above range, which can further improve the floating charge performance, high temperature safety performance and puncture safety performance of the electrochemical device. In particular, when the maximum particle size Dμm of the first polymer is regulated within the above range, it is beneficial to better improve the floating charge performance, high temperature safety performance and puncture safety performance of the electrochemical device.

[0098] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the principles of the present application should be included in the protection scope of the present application.

Claims

1. An electrochemical device comprising a positive electrode, a negative electrode and an electrolyte, characterized in that: The positive electrode comprises a positive electrode current collector and a positive electrode mixture layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode mixture layer comprises a first polymer and carbon nanotubes; the first polymer comprises nitrogen, oxygen and carbon; The infrared spectrum of the positive electrode mixture layer includes characteristic peaks of cyano and carbonyl. The characteristic peak of cyano is located at 2235 cm -1 Up to 2250cm -1 The characteristic peak of the carbonyl group is located at 1675 cm -1 Up to 1700cm -1 ; The peak intensity ratio of the characteristic peaks of the cyano group and the carbonyl group is A, 1≤A≤4; The aspect ratio of the carbon nanotube is B, 10≤B≤500.

2. The electrochemical device according to claim 1, characterized in that The electrochemical device satisfies at least one of the following conditions: (1) 150 ≤ A × B ≤ 400; (2)1≤A≤2; (3)100≤B≤300。 3. The electrochemical device according to claim 1, characterized in that The positive electrode mixture layer further includes lithium cobalt oxide. Based on the total number of particles in the positive electrode mixture layer, the number of particles of the first polymer accounts for K1%, and the number of particles of the lithium cobalt oxide accounts for K2%. The electrochemical device satisfies at least one of the following conditions: (1) 33 ≤ K2 / K1 ≤ 10000; (2)0.01≤K1≤1; (3)98≤K2≤99。 4. The electrochemical device according to claim 1, characterized in that Based on the total mass of the carbon element, the nitrogen element and the oxygen element, the first polymer satisfies at least one of the following conditions: (1) The mass percentage of the nitrogen element is H1%, 5≤H1≤20; (2) The mass percentage of the oxygen element is H2%, 5≤H2≤20; (3) The mass proportion of the carbon element is H3%, 60≤H3≤90.

5. The electrochemical device according to any one of claims 1 to 4, characterized in that The first polymer includes a first monomer, a second monomer, and a third monomer; The first monomer is selected from at least one of acrylonitrile or methacrylonitrile; The second monomer is selected from at least one of methyl acrylate, ethyl acrylate, propyl acrylate, isopropyl acrylate, isobutyl acrylate, tert-butyl acrylate, isoamyl acrylate, n-hexyl acrylate, 2-ethylhexyl acrylate, methyl methacrylate, ethyl methacrylate, propyl methacrylate, isopropyl methacrylate, isobutyl methacrylate, tert-butyl methacrylate, isoamyl methacrylate, n-hexyl methacrylate, or 2-ethylhexyl methacrylate; The third monomer is selected from at least one of acrylic acid, methacrylic acid, lithium acrylate, sodium acrylate, lithium methacrylate or sodium methacrylate.

6. The electrochemical device according to claim 5, characterized in that Based on the mass of the first polymer, the first polymer satisfies at least one of the following conditions: (1) The mass proportion of the first monomer is M1%, 50≤M1≤90; (2) The mass proportion of the second monomer is M2%, 1≤M2≤30; (3) The mass proportion of the third monomer is M3%, 5≤M3≤30.

7. The electrochemical device according to claim 5, characterized in that The first polymer further includes a fourth monomer, the fourth monomer being selected from at least one of acrylamide, N-methylacrylamide, N-ethylacrylamide or 2-methylacrylamide; Based on the mass of the first polymer, the mass proportion of the fourth monomer is M4%, 0.01≤M4≤15, preferably 1≤M4≤15.

8. The electrochemical device according to any one of claims 1 to 4, characterized in that: The maximum particle size of the first polymer is D μm, 15≤D≤100; preferably 15≤D≤50.

9. The electrochemical device according to any one of claims 1 to 4, characterized in that: The electrolyte includes ethylene carbonate, propylene carbonate and fluoroethylene carbonate.

10. An electronic device, characterized in that: An electrochemical device comprising any one of claims 1 to 9.

Citation Information

Patent Citations

  • Electrochemical element electrode composition, electrochemical element electrode, electrochemical element, and method for producing electrochemical element electrode composition

    CN107710468A

  • Composition for electrochemical element electrode

    CN115084525A

  • Positive electrode for lithium ion secondary battery and lithium ion secondary battery

    JP2014203804A

  • Electrode for non-aqueous electrolyte secondary battery

    JP2022077732A

  • Composition for electrochemical device electrode, electrode for electrochemical device, electrochemical device, and method of producing composition for electrochemical device electrode

    US20240128459A1